Titanium carbide and titanium aluminium carbide saturable absorbers fpr pulse generation in erbium-doped fiber lser - Jafry, Afiq Arif Aminuddin (2022)
The nonlinear optical properties of various materials have been widely investigated to develop an all-fiberized laser cavity. The existing saturable absorber (SA) materials own a few limitations such as band gap-dependent wavelength, narrow lasing bandwidth, low optical damage tolerance, and weak nonlinear absorption. Hence, this study has developed MXene Ti3C2Tx and MAX phase Ti3AlC2 as SA in a fiber laser cavity. The SA materials were prepared by a solution casting method and the D-shaped fiber was fabricated by using a mechanical wheel technique. The SA materials were characterized using field-emission scanning electron microscopy, energy-dispersive x-ray spectrometer, and Raman spectroscopy to confirm their elemental constituent. A twin-balanced detector technique examined the nonlinear absorption of SA devices, while linear absorption measurement confirmed the operating wavelength of the SAs. Linear and nonlinear absorption of the prepared SA devices exposed strong saturable absorption properties in the 1.55-μm region. An erbium-doped fiber laser cavity was developed and optimized to generate a continuous-wave laser. The Q-switched and mode-locked lasers were successfully generated using the SAs developed based on D-shaped fiber and thin film structure in the erbium-doped fiber laser cavity, indicating the compatibility of such SA devices in the all fiber-based cavity. The SA device with the highest nonlinear absorption of 3% was realized with MXene Ti3C2Tx coated on D-shaped fiber. All SA devices own strong optical properties, thus generating powerful Q-switched and mode-locked lasers. An improvement in the pulsed laser's parameters and nonlinear absorption properties of the material was achieved with D-shaped fiber as SA in the laser cavity. The MAX phase Ti3AlC2 deposited onto D-shaped fiber generated a mode-locked laser with a pulse width of 2.21 ps compared to its thin film counterparts, which initiated a mode-locked laser with a 3.68 ps pulse width. The use of ternary metal carbides, which are MXene Ti3C2Tx and MAX phase Ti3AlC2, proved the development of a SA with strong nonlinear absorption, high optical damage threshold, band gap-independent wavelength, and broad operational bandwidth. The short-pulsed lasers in the 1.55-μm regime are essential for various applications such as optical fiber communications, remote sensing, material processing, and laser cutting technology.